Does E-cigarette Use at Baseline Influence Smoking Cessation Rates among 2-Year College Students?. (28th June 2017) - Snow, Erika; Johnson, Tye; Ossip, Deborah J.; Williams, Geofrey C.; Ververs, Duncan; Rahman, Irfan; McIntosh, Scott
Abstract : Introduction: This study evaluates the association of baseline e-cigarette use with smoking cessation in a sample of 2-year college student smokers. Methods: Participants were 1, 400 students from over 60 2-year colleges across 25 states who were current smokers enrolled in a web-assisted tobacco intervention (WATI) trial. Survey data at baseline, 1-, and 6-months, were evaluated. Results: At 6-months, baseline e-cigarette users were more likely to report cessation of traditional cigarettes compared to non-users (OR 1.39, 95% CI 1.002–1.92). Cessation was also associated with higher baseline confidence in quitting and greater time to first cigarette after awakening. Baseline e-cigarette use was not associated with self-reported cessation of all nicotine/tobacco products (OR 1.09, 95% CI 0.75–1.58) nor biochemically verified cessation of all nicotine/tobacco products (OR 0.83, 95% CI 0.47–1.47). Higher confidence was again associated with both self-reported and biochemically verified cessation of all nicotines.